Parathyroid hormone is associated with the LV mass after aortic valve replacement. Issue 23 (5th August 2014) - Laflamme, Marie-Hélène; Mahjoub, Haifa; Mahmut, Ablajan; Boulanger, Marie-Chloé; Larose, Eric; Pibarot, Philippe; Mathieu, Patrick
Abstract : Aims: LV hypertrophy (LVH) is frequent after aortic valve replacement (AVR) and is often associated with comorbidities, including hypertension, obesity, renal failure and prosthesis-patient mismatch (PPM). However, whether other biological mechanism(s) may participate to LVH after AVR is still unknown. Parathyroid hormone (PTH) may play a role in LVH. However, it is presently unknown whether PTH is associated with LVH in patients that have undergone an AVR. Methods: In this cross-sectional study, 195 patients have been investigated at a mean of 8±3.5 years following AVR. LV function and mass were evaluated by Doppler echocardiography. The plasma levels of PTH, 25-hydroxyvitamin D (25-OHD), calcium and phosphate were measured. Results: There were 102 (52%) patients with LVH after AVR. In univariate analyses, PTH blood level was associated with LV mass (LVMi) and LVH. After adjustment for other risk factors, elevated PTH remained associated with LVMi (p=0.003) and LVH (p=0.02). In turn, the blood levels of 25-OHD and the renal function (GFR) were independently and inversely related to the blood level of PTH. Conclusions: After AVR, the level of PTH is independently associated with LVH. In turn, the level of PTH is related with the renal function and the level of 25-OHD.